Expression Analysis and Nuclear Import Study of Full-length Isoforms Importin α as 6x Histidin-tagged Fusion Protein on the Intracellular Localization of Recombinant HBV Core Protein - Aris Haryanto (Indonesian Journal of Biotechnology, 2005)
Isoform importin α molecules play a central role in the classical nuclear import pathway, that occurs through the nuclear pore complex (NPC) and typically requires a specific nuclear localization signal (NLS). In this study, it was investigated the role of isoforms importin α in the nuclear import of wild type recombinant hepatitis B virus core protein (WT rHBc), phosphorylated recombinant HBV core (rHBc) and recombinant HBV core without NLS by co-immunoprecipitation. Four recombinant full-length isoforms importin α as 6x histidin-tagged fusion protein were expressed and analysed from expression plasmid vectors Rch1, pHM 1969, pHM 1967 and pHM 1965. The results indicated that importin α-1, importin α-3, importin α-4 and importin α-5 can be expressed and isolated from E. coli transformed recombinant DNA plasmid as protein in size around 58-60 kDa. By the nuclear transport study shown that isoforms importin α are involved in the nuclear import of WT rHBc, phosphorylated rHBc and rHBc without NLS. It also indicated that they have an important role for nuclear transport of from cytoplasm into the nucleus.